Which STEM majors enroll in online courses, and why should we care? The impact of ethnicity, gender, and non-traditional student characteristics. (September 2015) - Wladis, Claire; Hachey, Alyse C.; Conway, Katherine
Abstract: Using data from roughly 27, 800 undergraduate STEM (science, technology, engineering and mathematics) majors in the National Postsecondary Student Aid Study (NPSAS), this research examines the relationship between race/ethnicity, gender and non-traditional student characteristics and online course enrollment. Hispanic and Black STEM majors were significantly less likely, and female STEM majors significantly more likely, to take online courses even when academic preparation, socioeconomic status (SES), citizenship and English-as-second-language (ESL) status were controlled. Furthermore, non-traditional student characteristics strongly increased the likelihood of enrolling in an online course, more so than any other characteristic, with online enrollment probability increasing steeply as the number of non-traditional factors increased. The impact of non-traditional factors on online enrollment was significantly stronger for STEM than non-STEM majors. Highlights: Hispanic and Black STEM majors were significantly less likely to enroll online. Female STEM majors were significantly more likely to enroll online. STEM majors with non-traditional characteristics were more likely to enroll online. Non-traditional characteristics predict online enrollment more than other factors. Non-traditional characteristics were more significant for STEM than non-STEM majors.